Hubungan Peran Orang Tua Dan Teman Sebaya Dengan Perilaku Berisiko Tertular HIV pada Remaja Gen Z Di Kabupaten Halmahera Utara - Sela Mariana Mangoto; Siti Maimunah; Sunartono (STIKES Ngesti Waluyo, 2025)
HIV/AIDS remains a significant global health problem and continues to be a serious issue in Indonesia, including North Halmahera Regency. Based on data from Tobelo Regional General Hospital, 26 HIV cases among senior high school students were recorded over the past six years, with an equal distribution of 13 males and 13 females. These cases were associated with homosexual orientation, vertical transmission, and high-risk sexual behaviors or free sex. This study aimed to analyze the relationship between parental roles and HIV risk behaviors in North Halmahera Regency. The study employed a descriptive correlational design with a cross-sectional approach. A total sample of 226 Generation Z students aged 15–18 years was selected using purposive sampling. The research instrument consisted of a closed-ended questionnaire. Data analysis included univariate and bivariate analyses. Bivariate analysis using the Spearman Rho test showed no significant relationship between parental roles and HIV risk behaviors (p = 0.557; r = −0.039). In contrast, a significant relationship was found between peer influence and HIV risk behaviors (p = 0.000; r = −0.515). In conclusion, there was no relationship between parental roles and HIV risk behaviors among Generation Z adolescents; however, a significant relationship was found between peer influence and HIV risk behaviors among Generation Z adolescents in North Halmahera Regency.